2000
DOI: 10.1016/s0735-1097(99)00639-7
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and late outcomes after direct stent implantation without balloon predilation

Abstract: The in-hospital and long-term clinical outcomes in patients undergoing a coronary intervention are equivalent when comparing stenting without balloon predilation with balloon angioplasty followed by stenting. Direct stenting is associated with decreased utilization of contrast agent and equipment and shorter procedure times. A randomized study should be performed to better determine the impact of this technique on short- and long-term procedural outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
2
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 15 publications
6
44
2
2
Order By: Relevance
“…The coiled design of this stent does not completely eliminate tissue prolapse or recoil and its relatively small radial strength has prompted its use after an aggressive predilatation. These latest unfavorable characteristics did not affect our procedural success that was possible in a larger number of lesions (97.9%) compared with previous studies [5,6,17,18].…”
Section: Choice Of Stentmentioning
confidence: 46%
See 1 more Smart Citation
“…The coiled design of this stent does not completely eliminate tissue prolapse or recoil and its relatively small radial strength has prompted its use after an aggressive predilatation. These latest unfavorable characteristics did not affect our procedural success that was possible in a larger number of lesions (97.9%) compared with previous studies [5,6,17,18].…”
Section: Choice Of Stentmentioning
confidence: 46%
“…So far, it has been reported that the advantages of the direct stenting strategy mostly rely on cost and radiation exposure reduction [17,18], but no data have been reported on angiographic flow. The main finding of the present study is that direct stenting determines a significant improvement of angiographic flow than standard stenting.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there were only 3 patients (2%) in Group A who underwent direct stent implantation without predilation. Previous studies [25][26][27][28][29] have demonstrated that direct stenting without balloon predilation reduces the slow flow and no-reflow phenomena and therefore, direct stenting might have influenced the achievement of blush-3 in this study.…”
Section: Study Limitationsmentioning
confidence: 73%
“…This observational study showed that direct stent implantation using a 5F guiding catheter and the transradial approach is feasible, safe, and effective, achieving a very low complication rate, almost zero. Other studies have already demonstrated that direct stent implantation without predilation is a safe and effective technique [7][8][9][10] , but the use of a 5F guiding catheter and the transradial approach has been demonstrated only in a series of patients selected with acute ischemic syndromes 11 .…”
Section: Discussionmentioning
confidence: 99%